Dietary Supplementation of Arugula (Eruca sativa) and Ginger: Effects on Egg Sensory Quality, Carcass Characteristics, and Reproductive Traits in Laying Hens - Albayati, Husham Jaafar Musa; Hassan, Shahla Fathola; Zinalabidin, Mohammed Madhi (Journal of Science in Medicine and Life, 2026)
The current research was conducted in an attempt to determine the impact of dietary enrichment of Eruca sative and ginger on egg formation, carcass structure, and reproductive performance of laying hens. Eighty four visceral ISA Brown laying hens (24 weeks old) were randomly assigned in a complete-block trial to seven dietary treatments. They included a basal control diet, diet containing 0.1 or 0.2 ginger as diet supplements, diet containing 0.1 or 0.2 arugula as diets supplements, and a diet containing arugula and ginger at 0.1 or 0.2 as diet supplements. The quality of eggs was measured in a nine-point hedonic scale that measured the appearance, colour, odour, flavour, colourfulness, and oxygenity. At the end of the experiment, carrass parameters, organ weights, and productive tract parameters were measured, but also reproductive parameters like the weight of ovarian, oviductal, and follicular weight were recorded. The findings showed that arugula and ginger supplementation did not result in any significant changes on the most carcass traits (P > 0.05), but there were differences in abdominal fat deposition and weights of the chosen body organs (P < 0.05). The influence on the measured reproductive parameters was not determined as significant. To sum up, arugula and ginger dietary supplementation have no negative impact on laying hens. It has no adverse effect on the sensory quality and reproductive performance of eggs, but can affect certain carcass and metabolic characteristics.